1987
DOI: 10.1136/pgmj.63.744.867
|View full text |Cite
|
Sign up to set email alerts
|

Severe reversible cardiac failure associated with methanol intoxication

Abstract: Summary:Methanol intoxication produces a well recognized clinical picture characterized by gastrointestinal, ocular and nervous system symptoms. The effect of poisoning on the cardiovascular system has not been well documented.We report the case of a 55 year old man whose acute methanol intoxication caused severe reversible cardiac failure. This represents the first description of an association between methanol toxicity and acute cardiac dysfunction in man.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 1 publication
0
14
0
1
Order By: Relevance
“…One case report documented a patient with methanol overdose that developed right bundle branch block in addition to left anterior fascicular block, paroxysmal atrial fibrillation and increased left ventricular end-diastolic and end-systolic dimensions [6]. In a case series of 8 men with methanol overdose published by Weisberger and Maclaughlin [7], ECG changes were observed in 7 men and these [8], described right atrial overload with tall peaked P-waves, clockwise rotation with a shift of transitional zone to the right, and right ventricular strain with tall R-waves in the right precordial leads [8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One case report documented a patient with methanol overdose that developed right bundle branch block in addition to left anterior fascicular block, paroxysmal atrial fibrillation and increased left ventricular end-diastolic and end-systolic dimensions [6]. In a case series of 8 men with methanol overdose published by Weisberger and Maclaughlin [7], ECG changes were observed in 7 men and these [8], described right atrial overload with tall peaked P-waves, clockwise rotation with a shift of transitional zone to the right, and right ventricular strain with tall R-waves in the right precordial leads [8].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is some disparity in our results as compared to what has been reported previously in the literature. The study by Cavalli et al [6] focused on describing the possible relationship between methanol intoxication and cardiac dysfunction. As such, the authors reported some ECG changes as part of the description.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, no literature has considered electrocardiographic (ECG) abnormalities as potential mortality predictors. Articles that do report ECG changes in patients poisoned with methanol are inconsistent (7,(22)(23)(24)(25)(26). In addition, little is known about the relationship between ECG parameters and metabolic/electrolyte disturbances as well as the signs and symptoms of methanol poisoning.…”
mentioning
confidence: 99%